We Live around Lake Baikal: Russians in Siberia - Brazhnikova, Inessa (project baikal, 2015)
It is a new issue of the series of mini-books about culture, traditions and customs of the inhabitants of Pribaikalie - “We Live around Lake Baikal” - published by the Irkutsk Regional Children’s Library named after Mark Sergeev. The issue is about the emergence of Russians in Eastern Siberia, their culture, traditions and family life.
Keywords: Siberia; Russians; explorers; indigenous people; traditions and customs